Pulsatile Drug Delivery Systems of Esomeprazole: Optimization through Quality by Design - Kurapati, Phaneendra; Chinni, Santhivardhan (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: The current research work was aimed to optimize and develop Pulsatile Drug Delivery Systems (PDDS) of esomeprazole so as to control the nocturnal acid breakthrough in ulcer patients. Materials and Methods: Microparticles separately for Delayed Immediate Release (DIR) and Delayed Extended Release (DER) were developed. DER microparticles were developed as matrix microspheres by optimizing different formulation and process parameters followed by enteric coating of the optimized formulation. Stirring speed, amount of Eudragit RSPO, type and amount of hydrophilic polymer were taken as the independent factors. Particles size and drug release at various characteristic time points were taken as the response variables. Central composite design was employed to elucidate the effect of the factors on the responses followed by optimization. Results: Except stirring speed on the drug release, all the other factors were observed to have significant effect (p<0.05) on all the responses. The SEM images described the mechanism responsible for delayed extended release of the esomeprazole. The results of graphical optimization indicated that the microspheres prepared with Eudragit RSPO at 0.67 g and polyethylene oxide at 0.33 g for 1 g of esomeprazole at 550 rpm as the optimized formulation. This formulation upon terminal enteric coating exhibited delayed release for an extended period of 6 hr, later the drug was released within 2 hr. Conclusion: Equal doses of simple enteric coated drug particles as DIR microcapsules along with the optimized DER microspheres could release esomeprazole effectively as two different pulses at the desired time intervals upon oral administration.
Keywords: Pulsatile drug delivery systems; Esomeprazole; Nocturnal acid breakthrough; Central; composite design; Optimization